The importance of N-linked glycosylation on the N-domain of angiotensin-I converting enzyme - Anthony, Colin Scott (Division of Medical Biochemistry, 2014)
Angiotensin-I converting enzyme (ACE) is an important drug target in the treatment of heart disease due to its role in the regulation of blood pressure. ACE contains two domains, the N- and C-domains, both of which are catalytically active and heavily glycosylated. Glycosylation is one of the most important forms of post-translational modification, having a wide range of functions including protein folding, modulation of the immune response, and providing targeting signals. Glycosylation is required for the expression of active ACE and structural studies of ACE have been fraught with severe difficulties because of surface N-glycosylation of the protein. This problem has been addressed to a large extent with respect to the C-domain, where the role of glycosylation has been extensively characterised and a minimally glycosylated form was able to crystallise reproducibly. As yet, little is known about the degree and importance of N-linked glycosylation on the N-domain. The generation of minimally glycosylated N-domain, however, requires a greater understanding of the relative importance of the individual N-linked glycosylation sites.